The dynamic instability of microtubules is not modulated by alpha-tubulin tyrosinylation. - Idriss, H; Stammers, D; Ross, C; Burns, R (1991)
The tyrosinylation of chick brain alpha-tubulin and the effects of the tyrosinylation status on the assembly and dynamic instability of chick brain MAP2:tubulin microtubule protein have been examined. Each of the eight major alpha-isotypes can be tyrosinylated in vitro, irrespective of whether a C-terminal tyrosine is genetically encoded. The extent of tyrosinylation is however limited to congruent to 0.3 mol.mol-1. The tyrosinylation status (0 vs. 0.3 mol.mol-1) has no effect on either the assembly kinetics of chick brain microtubule protein or on the rate of length redistribution following assembly and shearing. It is therefore unlikely that the tyrosinylation status directly affects the intrinsic stability of assembled microtubules since the rate of length redistribution is both a sensitive assay and a function of the kinetic parameters governing dynamic instability.